Penguatan Peran Orang Tua Melalui Pendidikan Ahlak dan Potensi Akademik Berbasis Keluarga - Indah Panglipur; Septi Triyani; Firman Ashadi; Mochammad Maulana Trianggono (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The role of parents in their children's moral and academic education is key in the formation of a generation of character and achievement. Islamic values provide holistic guidance for parents to assist their children in instilling noble morals while achieving academic success. This article aims to describe the implementation of a workshop designed to increase parents' understanding and involvement in educating their children based on Islamic values. The activity involved interactive sessions, group discussions and practical simulations to provide participants with practical insights. The results of the workshop showed an increase in parents' awareness of the importance of their role in supporting their children's education, both morally and academically. In addition, participants were able to identify concrete strategies that can be applied in daily life to strengthen Islamic value-based education. Thus, this activity contributes to the empowerment of parents as the main partners in building a superior and noble generation.